Aridity modulates belowground bacterial community dynamics in olive tree. (24th September 2021) - Marasco, Ramona; Fusi, Marco; Rolli, Eleonora; Ettoumi, Besma; Tambone, Fulvia; Borin, Sara; Ouzari, Hadda‐Imene; Boudabous, Abdellatif; Sorlini, Claudia; Cherif, Ameur; Adani, Fabrizio; Daffonchio, Daniele
Summary: Aridity negatively affects the diversity and abundance of edaphic microbial communities and their multiple ecosystem services, ultimately impacting vegetation productivity and biotic interactions. Investigation about how plant‐associated microbial communities respond to increasing aridity is of particular importance, especially in light of the global climate change predictions. To assess the effect of aridity on plant associated bacterial communities, we investigated the diversity and co‐occurrence of bacteria associated with the bulk soil and the root system of olive trees cultivated in orchards located in higher, middle and lower arid regions of Tunisia. The results indicated that the selective process mediated by the plant root system is amplified with the increment of aridity, defining distinct bacterial communities, dominated by aridity‐winner and aridity‐loser bacteria negatively and positively correlated with increasing annual rainfall, respectively. Aridity regulated also the co‐occurrence interactions among bacteria by determining specific modules enriched with one of the two categories ( aridity‐winners or aridity‐losers ), which included bacteria with multiple PGP functions against aridity. Our findings provide new insights into the process of bacterial assembly and interactions with the host plant in response to aridity, contributing to understand how the increasing aridity predicted by climate changes may affect the resilience of the plant holobiont.